Mapping Elementary Students’ Numeracy Literacy Skills: A Comprehensive Analysis Based on Six Indicators - Ardi Dwi Susandi; Thesa Kandaga; Hasan Basri; Vivi Rindastri (FOUNDAE (Foundation of Advanced Education), 2025)
Developing students’ numeracy literacy skills is essential in the 21st century, as these skills enable learners to interpret quantitative information, solve real-world problems, and make reasoned decisions. However, the mastery of numeracy literacy among elementary students in Indonesia remains uneven across regions. This study aimed to analyze the numeracy literacy skills of elementary school students in Region III Cirebon to identify their strengths and weaknesses across different competency indicators. A qualitative descriptive approach was employed, involving five elementary schools representing the region. Data were collected through numeracy literacy tests and semi-structured interviews. The instrument was developed based on six indicators: communication, representation, reasoning and argumentation, mathematization, problem-solving strategy, and the use of symbolic, formal, and technical operations. Data were analyzed through data reduction, data presentation, and conclusion drawing. The findings showed that students’ overall numeracy literacy skills ranged from medium to low levels. Communication skills were relatively strong, while reasoning, argumentation, and problem-solving strategies were moderate. In contrast, mathematization and symbolic operation skills were notably weak. These findings suggest that numeracy learning in elementary schools still emphasizes procedural understanding rather than conceptual and contextual reasoning. The study contributes to educational research by providing empirical evidence of the current state of numeracy literacy in elementary schools and offers implications for curriculum development and teacher training aimed at fostering deeper mathematical understanding and application.